Helmintos parásitos de la rata Sigmodon hispidus (Rodentia: Cricetidae) de un hábitat estacional y otro perenne en Costa Rica - Rodríguez, Beatriz (2000)
The helminthologicaI fauna of the cotton rat, Sigmodoll hispidus in a tropical environment varíes according to habitat and feeding behavior. Six species of nematodes (Longistriata adunca, Trichostrongylus sigmodontis, Strongyloides sigmodontis, Litomosoides carinií, Monodontus sp. and Protospirura sp.) and two species of cestodes (Hymenolepis diminuta and Raillietina sp.) were found in rats from extensive dry lands in Guanacaste where hot temperatures and heterogeneous diet are the rule. Only two species of nematodes (Longistriata adunca and Angiostrongylus costaricensis) were found in rats collected in a humid pineapple plantation in the Central Plateau (Alajuela) where mild temperatures predominate. A. costaricensis, a metastrongylid of medical importance, was found in 42 % of them.